A Rare Case of Acute Hemolytic Anemia in a Patient with Newly Diagnosed Multiple Myeloma: Maintaining a Fine Balance between Occam's Razor and Hickam's Dictum - Ovett, Jerin; Karunakaran, Parathan; Kalaiyarasi, Jayachandran Perumal; Devi, Deepa; Bommannan, Karthik; Gopisetty, Gopal; Mehra, Nikita (Indian Journal of Medical and Paediatric Oncology, 2022)
Anemia is a common feature in multiple myeloma and is multifactorial. A 52-year-old lady was admitted to our hospital with complaints of fatigue, exertional dyspnea, paresthesia, and a recent-onset confusion state. Fundus examination revealed features of hyperviscosity. The patient received 2 units of packed red blood cell transfusion (PRBC) before the present hospital admission. Laboratory investigations revealed severe anemia and thrombocytopenia. The M-protein was 5.8 g/dL. Bone marrow showed sheets of plasma cells. Immunofixation electrophoresis confirmed the presence of an IgAλ band. FISH was positive for IgH-FGFR3 fusion. The investigations confirmed multiple myeloma R-ISS stage III. The patient was immediately started on CyBorD chemotherapy regimen. The patient had indirect hyperbilirubinemia and symptomatic anemia. Initial testing of the patient's sample showed blood grouping discrepancy with DCT, ICT, and auto control positive. The symptomatic anemia persisted requiring PRC transfusions. Further antibody study revealed the presence of anti-Jka antibody—a warm IgG antibody and cold antibody. Subsequently, the patient received Jka antigen-negative B-positive compatible PRBC transfusions and the hemoglobin normalized. Our patient had transfusion-associated alloimmunization along with hyperviscosity. The timely recognition and early institution of plasmapheresis and myeloma-directed therapy along with transfusion of compatible Jka antigen-negative PRBC lead to rapid improvement.
Keywords: alloimmunization; anti-Jka; cold antibody; multiple myeloma